Reinventing foreign aid for inclusive and sustainable development: a survey - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2014)
This survey essay reviews over 200 papers in arguing that in order to achieve sustainable and inclusive development, foreign aid should not orient developing countries towards industrialisation in the perspective of Kuznets but in the view of Piketty. Abandoning the former's view that inequality will fall with progress in industrialisation and placing more emphasis on inequality in foreign aid policy will lead to more sustainable development outcomes. Inter alia: mitigate short-term poverty; address concerns of burgeoning population growth; train recipient governments on inclusive development; fight corruption and mismanagement and; avoid the shortfalls of celebrated Kuznets' conjectures. We discuss how the essay addresses post-2015 development challenges and provide foreign aid policy instruments with which discussed objectives can be achieved. In summary, the essay provides useful policy measures to avoid past pitfalls. 'Output may be growing, and yet the mass of the people may be becoming poorer' (Lewis, 1955). 'Lewis led all developing countries to water, proverbially speaking, some African countries have so far chosen not to drink' (Amavilah, 2014). Piketty (2014) has led all developing countries to the stream again and a challenging policy syndrome of our time is how foreign aid can help them to drink.
Keywords: B20; F35; F50; O10; 330; Foreign aid; Piketty; Kuznets; Development